Penerapan Nilai IMTAQ Siswa Melalui Pembiasaan Penguatan Pendidikan Karakter (PPK) di SMPN 21 Malang - Qurroti A`yun; Zahra `Arih Wicahya; Kurnia, Laila Tasa (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
In the process of habituation in character building, Religious Education becomes a very important thing to become a personality who has a tolerant attitude and becomes an effective medium to live a real life. The existence of this character formation effort is in line with one of the habituation programs that have been carried out at SMPN 21 Malang which provides a space to form IMTAQ-valued personalities in their students. The method used is descriptive qualitative with the type of case study because it aims to describe the state of the field that has been observed in depth and present it analytically in the form of interpretation of existing problems based on data sources. The data collection technique used is the triangulation technique (using 3 techniques at once: namely observation, interviews through online media, and observation) and is also supported by fidelity recordings. As for the results of the data obtained, there is a habituation program in the formation of IMTAQ valuable characters through an activity called "Strengthening Character Education (PPK)" which aims to bring up the value of faith, gratitude for favors, and awareness as creatures of Allah SWT in the students' personalities. In the habituation program there are several supporting activities, such as: Morning Prayer Together, Dzuhur Prayer & Friday Prayer in Congregation, and Istigotsah and Tahlil routines every week. The habit of strengthening character education is based on the existence of social ethics and religious awareness as a source of strengthening character education.